Queering Transcultural Encounters Bodies, Image, and Frenchness in Latin America and North Africa - Navarro-Ayala, Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In a highly original and interdisciplinary work bridging French and Francophone studies, cultural studies, media studies, and gender and sexuality studies, Luis Navarro-Ayala examines the transnational queer body as a physical and symbolic entity intrinsically connected with space. Through a transcultural and intersectional approach to bodily representations, socioeconomic conditions, and postcolonial politics, Navarro-Ayala analyzes queerness and Frenchness in narratives from North Africa and Latin America, revealing that Frenchness is coded to represent a sexually deviant "Other." France and Frenchness, in two distinct regions of the global South, have come to represent an imagined queer space enabling sexual exploration, even in social conditions that would have otherwise prevented queer agency. .
1. The Garçonnière in Buenos Aires: The Queer Body as a Boundary Figure in "Frenchness": The Transnational Queer in Alfonso Hernández-Catá's El ángel de Sodoma -- 2. Othering the Contemporáneos: Frenchness, Mexicanness and Queerness -- 3. Moroccan Boys: Points of Resistance in Homosexual Tourism -- 4. Rachid O.'s Homosexual Awakening: The Allegorical Representation of the Blond-haired, Blue-eyed French Boy -- 5. Homoerotic Crossings: Corporeal Dis/Positions in Immigrations to Spain and France -- 6. The Queer Beur Look: Disidentification and Subversion in France -- 7. Queering the Football Field: Intersectionality and Transnationalism in the Maghreb.
Keywords: Human body -- Social aspects; Culture; Queer theory; Latin American literature; African literature; Literature, Modern -- 20th century; Sociology of the Body; Sociology of Culture; Queer Studies; Latin American/Caribbean Literature; African Literature; Twentieth-Century Literature